2014
DOI: 10.1002/nau.22616
|View full text |Cite
|
Sign up to set email alerts
|

Functional and anatomical differences between continent and incontinent men post radical prostatectomy on urodynamics and 3T MRI: A pilot study

Abstract: Aims There are competing hypotheses about the etiology of post prostatectomy incontinence (PPI).The purpose of this study was to determine the anatomical and functional differences between men with and without PPI. Methods Case control study of continent and incontinent men after radical prostatectomy who underwent functional and anatomic studies with urodynamics and 3.0 Tesla MRI. All men were at least 12 months post prostatectomy and none had a history of pelvic radiation or any prior surgery for incontine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 30 publications
3
37
1
Order By: Relevance
“…After the first study by Coakley et al, 18 recent studies have showed that preoperative MUL was associated with recovery of continence after radical prostatectomy. 13,16,[19][20][21] Our study not only confirmed their findings, but also evaluated the relationship between postoperative MUL and urinary continence. Our results showed that postoperative MUL was significantly associated with urinary continence recovery, indicating that residual MUL also influenced recovery of continence.…”
Section: Discussionsupporting
confidence: 82%
“…After the first study by Coakley et al, 18 recent studies have showed that preoperative MUL was associated with recovery of continence after radical prostatectomy. 13,16,[19][20][21] Our study not only confirmed their findings, but also evaluated the relationship between postoperative MUL and urinary continence. Our results showed that postoperative MUL was significantly associated with urinary continence recovery, indicating that residual MUL also influenced recovery of continence.…”
Section: Discussionsupporting
confidence: 82%
“…Outcome variables were similar to those described for MVC (Table ). Functional urethral length was calculated from a resting US image as the distance between the UVJ and the entry of the urethra at the penile bulb . This measure has been reported to be related to continence control.…”
Section: Methodsmentioning
confidence: 99%
“…Many factors have been suggested to explain some of the variation in symptoms of PPI. These include pre‐ and post‐surgical urethral length, prostate volume at time of surgery, age, denervation, BMI, and urethral stricture . Recent reviews have concluded that there is limited evidence to support the relationship between any one of these factors and incontinence .…”
Section: Introductionmentioning
confidence: 99%
“…In a remarkable topic article, Cameron et al [22] recently detailed the characteristics of sphincter anatomy and functional profiles on urodynamics during Kegel exercises in men with (n ¼ 14) and without PPI (n ¼ 12). They were able to show that patients with PPI were less able to increase urethral pressure during contraction of pelvic floor muscles but also a significantly shorter length of the urethral sphincter, a wider urethral lumen, and a higher distortion of the sphincter region on MRI.…”
Section: Additional Evaluationsmentioning
confidence: 99%